2004
DOI: 10.1104/pp.103.030577
|View full text |Cite
|
Sign up to set email alerts
|

The MADS Box Transcription Factor ZmMADS2 Is Required for Anther and Pollen Maturation in Maize and Accumulates in Apoptotic Bodies during Anther Dehiscence

Abstract: The maize (Zea mays) late pollen gene ZmMADS2 belongs to the MIKC type of MADS box transcription factor genes. Here, we report that ZmMADS2, which forms a homodimer in yeast (Saccharomyces cerevisiae), is required for anther dehiscence and pollen maturation. Development of anthers and pollen was arrested at 1 d before dehiscence in transgenic plants expressing the ZmMADS2-cDNA in antisense orientation. Temporal and spatial expression analyses showed high amounts of ZmMADS2 transcripts in endothecium and connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…Other MADS box genes, such as SPOROCYTELESS/NOZZLE (SPL/NZZ) (Yang et al, 1999;Schiefthaler et al, 1999) and AG (Ito et al, 2004(Ito et al, , 2007 from Arabidopsis and MADS2 from maize (Zea mays; Schreiber et al, 2004), have been implicated in regulating anther development. SPL/NZZ regulates the formation of anther walls and pollen mother cells, as the primary sporogenous cells cannot form pollen mother cells in spl anthers, thereby blocking early cell differentiation (Yang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other MADS box genes, such as SPOROCYTELESS/NOZZLE (SPL/NZZ) (Yang et al, 1999;Schiefthaler et al, 1999) and AG (Ito et al, 2004(Ito et al, , 2007 from Arabidopsis and MADS2 from maize (Zea mays; Schreiber et al, 2004), have been implicated in regulating anther development. SPL/NZZ regulates the formation of anther walls and pollen mother cells, as the primary sporogenous cells cannot form pollen mother cells in spl anthers, thereby blocking early cell differentiation (Yang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…During later developmental stages, AG continues its expression in the anther and regulates anther dehiscence by directly regulating the expression of the gene that encodes a jasmonic acid (JA) synthetic enzyme, DEFECTIVE IN ANTHER DEHISCENCE1 (Ito et al, 2007). Maize MADS2 is required for anther dehiscence and pollen maturation, and knockdown of MADS2 resulted in abortion of anthers and defective pollen development (Schreiber et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…With the progress in understanding of the control of MADS-box genes in organ differentiation of flowers in Arabidopsis, studies have been conducted to elucidate the relationship between the MADS-box genes and sex determination in economic crops with gender specificity, such as monoecious cucumber (Kater et al, 2001) and corn (Heuer et al, 2001;Schreiber et al, 2004), dioecious asparagus (Park et al, 2003), and trioecious papaya (Ackerman et al, 2008). Trioecious papaya is an economically important sub-tropical fruit crop, with its regular hermaphroditic flowers and production yield is emphasized in hermaphrodite papaya cultivation (Arkle Jr. and Nakasone, .…”
Section: Discussionmentioning
confidence: 99%
“…The putative ATG start codon is indicated by a black box a DEFH125 homolog from Zea mays, is also expressed in pollen and pollen tube but has evolved an additional function. ZmMADS2 expression is also transiently detectable in the endothecium and connective tissues of the anther (Schreiber et al 2004). Functional analysis showed that this gene not only plays a role in pollen maturation but is also involved in anther dehiscence (Schreiber et al 2004).…”
Section: Defh125 Promoter Drives Gus Expression In Pollen and Pollen mentioning
confidence: 99%